Seroprevalence of antibodies against Brucella sp. in cattle farmers in the San José de Lourdes district, Cajamarca, 2019 - Santa Cruz-López, Cinthya (2021)
Objective. To determine the seroprevalence of antibodies against Brucella sp. and to identify the predisposing factors and associated symptomatology in cattle farmers in the San José de Lourdes district (San Ignacio) in the department of Cajamarca, during the months of September to December 2019. Methods. The study was observational, cross-sectional, prospective with an exploratorydescriptive design. A  probabilistic sampling was carried out, where 147 blood serums belonging to cattle of both genders were analyzed. The seroprevalence of antibodies was determined by Rose Bengal and Huddleson antigen testsand a structured survey was applied to identify predisposing factors and symptoms associated with the disease. Results. It was found that 17% of cattle farmers seropositive for Brucella sp. had prolonged direct contact with cattle (p < 0.05). In addition, 23.8 % of farmers had antibodies against Brucella sp., being mainly women (15.6 %). Cattle farmers with antibodies against Brucella sp. consumed cheese (22.4 %), milk (19.7 %) and blood from slaughtered animals (17 %) (p > 0.05). The most recurrent symptoms were headache (19 %),fatigue (14.3 %), joint pain (13.6 %), fever and insomnia (10.2 %). Conclusion. The seroprevalence of antibodies against Brucella sp. is high and is associated with prolonged direct contact with cattle and symptoms such as headache and fever, present in the population evaluated. The results obtained show theworrying situation of the cattle farmers of San José de Lourdes, in addition to the scarce preventive culture that exists